Zulus ideas and symbolism - Berglund, Axel-Ivar (Social Anthropology, 2016)
The Zulu, numbering about 4 030 000 persons, are a Nguni people who live mainly in the province of Natal in the Republic of South Africa. It is this people that is described in the present study. The anthropological/ethnographic literature on the Zulu people is extensive. So is the linguistic and historical material. Written evidence has been made use of, particularly in instances where differences in rites, rituals, customs, ceremonies, symbols, etc. have been recorded. But because the study is focused on an understanding of patterns of behaviour, thought, and expression rather than description of them, the material on which the study is based is to a large extent my own fieldwork. The data presented is, from this angle of approach, original. Comparative evidence published on neighbouring Nguni peoples and other African peoples has been used as a guide in my own investigations and analysis of material collected in the field.